Temporal Changes in Concentrations of Some Trace Elements in Muscle Tissue of Crayfish, Astacus leptodactylus (Eschscholtz, 1823), from Keban Dam Lake - Onder Aksu; Ragip Adiguzel; Veysel Demir; Numan Yildirim; Durali Danabas; Sebahat Seker; Safak Seyhaneyildiz Can; Mustafa Ates (Bioinorganic Chemistry and Applications)
Crayfish (Astacus leptodactylus Eschscholtz, 1823) is the native crayfish species in Turkey. It was exported regularly to Western Europe. In this study, bioaccumulation and temporal trends of some trace elements (arsenic: As, cadmium: Cd, copper: Cu, mercury: Hg, lead: Pb, and zinc: Zn) in edible abdomen muscle of crayfish from Keban Dam Lake (Elazığ, Turkey) were investigated for the 2006–2012 period. Sequence of metal concentration levels was Zn > Cu > Hg > Pb > Cd > As in muscle tissues. The highest concentration of Zn (21.69 mg kg−1) was detected in 2006, while the lowest (4.35 mg kg−1) in 2009. In general, it was found that the concentrations of trace elements investigated were lower than the maximum permissible limits of the food regulations of the Ministry of Food, Agriculture, and Livestock (MFAL), the Turkish Food Codex and Commission Regulation (EC). If the crayfish selected for the study are recognized as bioindicators of environmental pollution, then it is possible to conclude that the changes in studied trace elements concentrations in the Keban Dam Lake are being steady.